The influence of human resource competence and budget planning in Kediri City - Lucyana; Djunaedi; Budi Rahayu (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
Effective budget management and absorption are essential to improve the quality of public services and achieve development goals. When budget management is not optimal, it can hinder development and reduce public trust in the government. This study highlights the importance of human resource (HR) competence and mature budget planning in overcoming the problem of uneven budget absorption, such as in the Kediri City Regional Secretariat Work Unit. This study uses multiple linear regression to analyze the influence of HR, budget planning, internal policies, and external factors on budget absorption. The research sample involved 68 employees tasked with budget management. Data analysis includes descriptive and inferential statistical tests to test the relationship between independent variables (HR, budget planning, internal policies, and external factors) and the dependent variable (budget absorption). The results showed that all variable items were valid with a Pearson Correlation value of 0.4–0.789, greater than the R table of 0.248. The measurement reliability is good with a Cronbach's Alpha value> 0.7. Partial test shows that HR (t count = 9.589) and budget planning (t count = 9.003) have a significant effect on budget absorption (significance 0.000). Simultaneous test shows a joint effect (F count = 169.093, F table = 3.14, significance = 0.000). The coefficient of determination (R² = 0.839) shows that both independent variables explain 83.9% of the variation in budget absorption.